กลยุทธ์การกำหนดนโยบายและการนำนโยบายสู่การปฏิบัติ สำหรับนโยบายการจัดหาเครื่องคอมพิวเตอร์แท็บเล็ตให้แก่โรงเรียน - ศรีดา ตันทะอธิพานิช (จุฬาลงกรณ์มหาวิทยาลัย, 2014)
This research aimed to study the current and the desirable states, to analyze the strengths, weaknesses, opportunities and threats and to develop strategies for policy formulation and implementation concerning the provision of tablet PC to schools. This study was conducted by using mixed research methods. The policy board members, 145 primary educational service area offices and 345 schools were used as research sample. The instruments were semi-structured interviews and questionnaire. The frequency, percentage, average, standard deviation, PNImodified and content analysis were used in the data’s analysis. The research findings showed that the politicians played the major role in policy formulation which aimed to provide one table PC per student without strategic planning based on research and less participation of stake holders. The overall view of the current states of policy implementation were at high level. The desirable states were the collaboration among policy implementation organizations on brainstorming, preparation inspecting, and planning with fully and continuously supports for any related resources from the ministry. It was found that the strengths were the policy with provides public benefits and interests, target and values setting, patterns of control, monitoring mechanisms and values for implementation enhancement while the weaknesses were lack of collaboration, success criteria definition and organizational procedures. The opportunities were the government education policies and technological advancement while the threats were the economic and social conditions. The policy formulation strategies were (1) to broadly and sustainably raise the level of policy acceptance (2) to identify the policy strategic directions concerning education and technology trends. The policy implementation strategies were (1) to assign the accountability chain for policy implementation of each organization level (2) to strict to good governance on policy implementation and (3) to create KPI target to improve students outcome.